An instructional exercise on target cost management: a customer centered product design approach - Nunes, Manuel L. (2009)
A Target Cost Management approach is customer, design, and process focus. The authors have developed an in-class exercise on TCM. This exercise can be used to involve students or practitioners in a dynamic process where a new product development (NPD) process is enhanced by the use of several cost management techniques. This exercise has been applied in the academic year of 2008/09 by two teams of students. The exercise was designed considering previous work [1-3]. Nevertheless, several changes, adaptations and improvements were made. This article presents the TCM exercise and discusses its implications. This work offers a basis for further replications in a classroom setting and also can be used to demonstrate the role of target costing in NPD processes to an audience of practitioners.